Novel recombinant cold-adapted alkaliphilic lipase (Glalip03) from Antarctic yeast, Glaciozyma antarctica PI12 - Matinja, Adamu Idris; Ahmad Kamarudin, Nor Hafizah; Leow, Adam Thean Chor; Oslan, Siti Nurbaya (Springer Science and Business Media Deutschland, 2024)
The present study investigates a novel low-temperature adapted lipase, Glalip03, from Glaciozyma antarctica. The gene was codon-optimised, synthesised, and heterologously expressed in E. coli strain Origami™ B (DE3) as a fusion with thioredoxin (Trx) using a pET32b (+) expression vector. The recombinant Trx-Glalip03 was expressed successfully in a soluble form with 0.1 mM concentration of isopropyl β-D-thiogalactopyranoside (IPTG) at 25 °C and post-induction time of 4 h. A one-step Nickel Sepharose affinity chromatography technique was used to purify the recombinant Trx-Glalip03 with an average molecular size of around 53 kDa. The purified Trx-Glalip03 was catalytically active against the hydrolysis of triglycerides and olive oil with a preference for triolein, tripalmitin, and tributyrin. The Trx-Glalip03 showed high stability under different organic solvents with temperature and pH optimum at 30 °C and 9.0, respectively. Furthermore, the Trx-Glalip03 catalytic activity was similarly influenced by metal ions and ethylenediaminetetraacetic acid (EDTA). The kinetic behaviour of the lipase reaction was described with Hill equation kinetics resulting in a dissociation constant (Kd) value of 0.32 g/mL and positive hill coefficient (n). These biochemical features of the recombinant lipase Trx-Glalip03 suggest that it is an effective and innovative biocatalyst for biotechnological and industrial applications.